Proposal of the Location and Shape of the Outrigger Arm and Belt Truss in the High-Rise Buildings with the Central Core - Gholamreza Abdollahzadeh; Hadi Faghihmaleki; Reza Alghosi (Numerical Methods in Civil Engineering)
The outrigger arm system and belt truss with braced core in the center of the structure surrounded by belts truss, is an efficient and reliable system for high-rise buildings against severe lateral forces such as earthquake and wind. The purpose of this research is investigating the outrigger arm system and belt truss with the braced core under lateral loads. Another purpose of this research is to reduce the drift and displacement of the roof against these loads with deformation and finding the optimal location for the outrigger arm by/through various methods. Analysis of nonlinear time history and spectral analysis of the site with a high relative risk for the three models of 30, 45, and 60 floors have shown that the optimum location of the outrigger arm and belt truss with the proposed method in this research has been better more noteworthy than the previous methods and caused decreasing as it has induced/brought about a decrease in absolute roof displacement and maximum relative displacement of floors. The suggested deformation for outrigger arm in addition to reducing the stress concentration in the floors where outrigger arm are is installed, has caused a significant reduction in the absolute change in the roof of the building and the maximum relative displacement of the floors.